2020
DOI: 10.29309/tpmj/2020.27.04.3436
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the nutritional status by measuring body mass index and screening of school going children of Khairpur Mirus Sindh.

Abstract: Objectives: To assess the Nutritional Status by measuring Body Mass Index and screening of School going children of Khairpur Mirus Sindh. Study Design: Cross Sectional Descriptive Study. Setting: Department of Pediatrics, Liaquat University of Medical and Health Sciences Jamshoro. Period: From 1st May to 31st May 2015. Material & Methods: Over 2400 children (age 5 to 18 years) studying at schools of Taluka Khairpur Mirus, Sindh. We conducted this study at 40 schools, both from government and private sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Globally, since the early 2000, for better and early management of malnutrition, community health workers diagnose the effected children with uncomplicated severe acute malnutrition and refer them to especially built health centers running specific outpatient therapeutic feeding programmes. 20 In Pakistan Salma Shaik 21 reported that, nutritional deficiency is responsible for school absence in 30% school going children. According to research results of Fatima Shahryar, 22 under five years…”
Section: Graph 1: Comparison Of Weight Among Government and Private School Childrenmentioning
confidence: 99%
“…Globally, since the early 2000, for better and early management of malnutrition, community health workers diagnose the effected children with uncomplicated severe acute malnutrition and refer them to especially built health centers running specific outpatient therapeutic feeding programmes. 20 In Pakistan Salma Shaik 21 reported that, nutritional deficiency is responsible for school absence in 30% school going children. According to research results of Fatima Shahryar, 22 under five years…”
Section: Graph 1: Comparison Of Weight Among Government and Private School Childrenmentioning
confidence: 99%